Multidimensional Sustainability Evaluation of Community-Based Material Recovery Facilities (TPS3R) and Strategies for Strengthening Regional Waste Management Systems: A Case Study in Mojokerto Regency - SYUKRON, MOCHAMAD (Directorate of Research and Community Service (DRPM), 2025)
Mojokerto Regency faces a significant waste crisis, with the Tempat Pengolahan Sampah Reduce-Reuse-Recycle (TPS3R) program contributing a negligible 0.015% to regional waste reduction. This failure suggests deep-seated systemic barriers beyond physical infrastructure. This study aims to analyze the sustainability status of the TPS3R program and formulate an integrated optimization strategy to achieve financial autonomy and institutional support. A quantitative assessment using Multidimensional Scaling (MDS) via RAPFISH was employed on a